2008
DOI: 10.1093/eurheartj/ehn427
|View full text |Cite
|
Sign up to set email alerts
|

Do men and women respond differently to blood pressure-lowering treatment? Results of prospectively designed overviews of randomized trials

Abstract: All of the blood pressure-lowering regimens studied here provided broadly similar protection against major cardiovascular events in men and women. Differences in cardiovascular risks between sexes are unlikely to reflect differences in response to blood pressure-lowering treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
145
0
14

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(169 citation statements)
references
References 55 publications
10
145
0
14
Order By: Relevance
“…31 However, a meta-analysis of data from 31 trials involving more than 100 000 male and nearly 90 000 female patients with hypertension found no evidence of a difference in the effects of BP-lowering treatment regimens between men and women. 21 In this study, there were no differences across subgroup categories in the incidence or type of adverse effects. Full tolerability data from this trial were previously reported 17 and were consistent with the safety profiles of angiotensin receptor blocker/calcium channel blocker combinations described in the literature.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…31 However, a meta-analysis of data from 31 trials involving more than 100 000 male and nearly 90 000 female patients with hypertension found no evidence of a difference in the effects of BP-lowering treatment regimens between men and women. 21 In this study, there were no differences across subgroup categories in the incidence or type of adverse effects. Full tolerability data from this trial were previously reported 17 and were consistent with the safety profiles of angiotensin receptor blocker/calcium channel blocker combinations described in the literature.…”
Section: Discussionmentioning
confidence: 49%
“…For example, certain BP-lowering treatment regimens have been reported to differ between men and women, [18][19][20] whereas others have shown no evidence of a gender difference. 21 Also, BP is known to increase with advancing age and it is important to determine that antihypertensive therapies are effective in older patients.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective was to quantify the effects of BP-lowering treatment according to gender and to determine whether there are important differences in the proportional benefits of treatment between women and men. 53 Despite baseline BP levels were slightly higher among women than men, there was no evidence that women and men present different levels of protection from total major CV events (stroke, coronary heart disease events, heart failure and other CV death) from BP lowering. Furthermore, the data showed no evidence of an interaction of sex with BP-lowering treatment for the outcomes of coronary heart disease, heart failure, CV death or total mortality.…”
Section: Gender Considerations In the Treatment Of Hypertensionmentioning
confidence: 94%
“…2,3 Whereas recent evidence suggests that the association of blood pressure (BP) and the risk of ischaemic heart disease and stroke is similar in men and women and that BP lowering provides broadly similar mortality benefits, irrespective of the drug regimen used, other data suggest potential gender differences with regard to treatment efficacy. [4][5][6][7] Furthermore, women with known cardiovascular disease or cardiovascular risk factors are less likely to receive guideline-recommended drug therapy as compared with men, and BP-control rates appear to be lower in women at a higher age. [8][9][10][11] As cardiovascular disease is considered to be the single largest cause of mortality in women with 70% of cardiovascular deaths attributable to modifiable risk factors, such as hypertension, it is important to better understand gender disparities in hypertension management on a worldwide basis to ensure equal standards in treatment for both, men and women.…”
Section: Introductionmentioning
confidence: 99%